Lanthanide-based complexes as efficient physiological temperature sensors - Monteiro, Bernardo (2022)
A new molecular thermometric sensor based on the terbium(III) complex [C2mim][Tb(fod)4] (C2mim – 1-methyl-3-ethylimidazolium, fod− - tetrakis-6,6,7,7,8,8,8-heptafluoro-2,2-dimethyl-3,5-octanedionate), doped with 0.015% of its europium(III) analogue (1, [C2mim][Tb(fod)4]0.99985:[C2mim][Eu(fod)4]0.00015), was prepared and its thermochromic behaviour evaluated from ambient temperature up to 75 °C, including in the physiological range (35–45 °C). It was found that the intensity ratio of the 5D4→7F5 (TbIII) and 5D0→7F2 (EuIII) transitions is correlated with temperature having three different linear regimes. Visual colorimetry allowed the evaluation of the temperature in different ranges from green at ambient temperature, to yellow and finally red at higher temperatures. The TbIII complex emission intensity is extremely sensitive to small temperature variations, particularly between 25 and 35 °C, were it reaches only 40% of the initial intensity. Confinement of the dopped TbIII tetrakis-complex in the organic polymeric matrix poly(methylmethacrylate) (PMMA) induced higher thermal stability in 1, together with a strong temperature dependence of the most intense emissive transition of the TbIII complexes. The photoluminescence quantum yield of polymer-lanthanide hybrid materials increased significantly compared with that of 1. Under 366 nm irradiation, the hybrid material presents a green colour at 25 °C that evolves to yellow at 30 °C and to a white tone at 35 °C.